Authorship Background and Language Aspects on Javanesse Drama Scripts by Cross-Generation Authors’ Work - Ucik Fuadhiyah; Hanifah Nur Insani; Dini Anggraheni (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
The process of reviewing the manuscript in detail and depth will result in a correct understanding and in accordance with the interpretation between the author, cultivator, and actor. The aim of this research article is to describe the form of linguistic aspects contained in Javanese drama scripts by authors across generations and to describe aspects of the authorship background contained in Javanese drama manuscripts by authors across generations. The approach used in this research is descriptive qualitative. Based on the results of the analysis and discussion on six Javanese drama scripts (Lelakon, Tuk, Dom, Tengara, Sumilir Angin Nang Brug Belis, and Mak Ana Asu Mlebu Ngomah) the works of these cross-generational authors who have the same or similar intrinsic elements even though each manuscript has its own characteristics and uniqueness.